Leadership and registered nurses (RNs) working after‐hours in Residential Aged Care Facilities (RACFs): A structured literature review. Issue 21 (24th July 2018) - Nhongo, Dorika; Hendricks, Joyce; Bradshaw, Julie; Bail, Kasia
Abstract : Aims and objectives: The aim of this literature review is to synthesise and analyse the literature pertinent to the RN's competence and confidence to undertake the leadership role when working in residential aged care facilities after‐hours and to determine any association of leadership with quality resident outcomes. Background: Registered nurses (RNs) working in Residential Aged Care Facilities are required to undertake complex management tasks including leading nursing care teams, supervising non‐nursing staff and allocating workloads according to residents' care needs, staff skills and experience. Registered nurses plan, assess, manage medication, evaluate each resident's care, liaise with doctors and allied health professionals and are responsible for evidence‐based practice in accordance with the Nursing Standards for Practice (2016). Researchers have commented that effective nurse leadership can improve quality of care, improved resident outcomes and reduce adverse events. Design: A review of original research papers based on the structured methodology described by Kable, Pich, and Maslin‐Prothero (Nurse Education Today, 32, 2012, 878‐886). Methods: The review was conducted according to the 12‐step structured framework by Kable et al. (Nurse Education Today, 32, 2012, 878‐886). The search included peer‐reviewed papers published between 2002–2017 on RN leadership after‐hours, factors contributing to or with relationships to nursing leadership. Nineteen papers were found that researched the impact of leadership in aged care settings. Results: The literature review concluded that nursing leadership has been linked to the quality of care and clinical outcomes in the aged care setting. However, RNs in the aged care setting have limited opportunities to develop key leadership competencies and confidence in order to meet the many challenges found in this environment due to lack of access to aged‐care‐specific leadership education. Minimal publications address the importance of the leadership of after‐hours RNs. Results from this literature review will inform future research in this area. Conclusion: Nineteen papers identified the leadership required of RNs in aged care settings. However, limited research investigating the association between nursing leadership and clinical outcomes was found. The findings from this literature review suggest that leadership in the aged care setting may be facilitated through specific educational activities such as RN shadowing shifts, continuing professional development, working with peers and by demonstrating and practising leadership competencies. Based on the literature reviewed, a need for more research in this area is required. In a specific manner, research into RN leadership, competence and confidence in aged care facilities after‐hours is needed. Relevance to clinical practice: Registered nurses working in the aged care setting after‐hours need access to leadership education. Better quality of care, improved resident outcomes and reduced adverse events are associated with sound leadership.